Is Obstructive Sleep Apnea-Associated Adenoid Hypertrophy Linked to Scoliotic Attitudes in Children? - Ugur, Fatih; Topal, Kubra; Albayrak, Mehmet; Topal, Murat (Springer Science and Business Media LLC, 2023)
Introduction Scoliosis, a multifaceted spinal deformity commonly affecting pediatric and adolescent populations, has spurred extensive scientific inquiry to understand its origins and impacts. Early-onset scoliosis (EOS), characterized by spinal curvature exceeding 10° before the age of 10, presents a unique challenge necessitating a comprehensive understanding of its etiological factors. Within this context, the potential role of hypoxia-induced by adenoid hypertrophy in contributing to the pathogenesis of EOS has emerged as an intriguing avenue of investigation. Materials and methods This retrospective study was conducted focusing on radiological and clinical data pertaining to children below 10 years of age who underwent isolated adenoidectomy for adenoid hypertrophy. Preoperative posteroanterior standing chest radiographs were utilized for scoliosis assessment, with Cobb angles serving as the primary measurement metric. To ensure accuracy and reliability, Cobb angle measurements were independently performed by two experienced observers. Statistical analyses encompassed the Mann-Whitney U test, Spearman correlation analysis, and intraclass correlation coefficient calculations to evaluate interobserver agreement. Results Among the cohort of 218 pediatric adenoidectomy patients, 177 individuals had radiographs suitable for EOS evaluation. The mean age of the participants was 5.72±2 years, with a nearly equal distribution of 52.5% male and 47.5% female patients. Strikingly, the study identified a 10.2% prevalence of coronal plane curvatures exceeding the critical threshold of 10°, indicative of EOS. The robust interobserver reliability was demonstrated by a commendable mean interclass correlation coefficient (ICC) value of 0.926, affirming consistent and accurate Cobb angle measurements between the observers. Conclusion In light of the heightened prevalence of EOS observed in children undergoing adenoidectomy, this study provides a compelling impetus for exploring the potential interrelationship between adenoid hypertrophy, hypoxia, and the emergence of early-onset scoliosis. The study underscores the importance of prospective research to elucidate the complex mechanisms connecting these factors, offering insights into potential risk factors and underlying pathogenic pathways associated with the development of early-onset scoliosis.
Keywords: Pediatrics; 3. Good health